Self-directed learning of preclinical medical students in Basic Surgical Skills through remote teaching - Aleta, Karlos Noel R.; Sana, Erlyn A. (Manila National Teacher Training Center for the Health Professions, University of the Philippines Manila, 2024)
Background: Due to the COVID-19 pandemic, face-to-face teaching in medical schools was stopped and was forced to go online. Preclinical year levels were not allowed to have patient encounters. The surgical skills which would have been taught face-to-face during clinics were suspended. Hence the need to give students opportunities to engage in Self-Directed Learning (SDL). SDL is a core construct of adult learning from which students can describe and be understood as they journey through medical education.

Objectives: The objectives of this study were to (1) determine the level of motivation and SDL of Year Level 3 medical students to study the Basic Surgical Skills by remote platform, (2) determine the performance of Year Level 3 medical students before and after completing the Online Basic Surgical Skills Module (OBSSM), and (3) correlate performance of Year Level 3 medical students in the OBSSM and their level of SDL.

Methodology: Participating medical students taking Surgery in a private medical school were asked to take a pre- test on an OBSSM as well as the Adult Learning Principles Design Elements Questionnaire (ALPDEQ), Participants were given the OBSSM to be completed on their own within two months. A post-test was administered after the given time frame. Participants who completed the module then completed the posttest.

Results: There were thirty-six participants who joined and two withdrew by the end of the study. The ALPDEQ scores all had values per construct ranging from 4-5 in the Likert scale with five as the most favored score. The 40-item multiple-choice pre- test scores initially had eleven participants passing. After completing OBSSM, twenty-seven participants passed the post- test. The obtained t-test was -5.75 with p=0.001. The correlation value between the post test scores and ALPDEQ scores was 0.3773 showing moderate correlation. The average screen time was 5 hours and 20 minutes per participant.

Discussion: The high ALPDEQ scores for all constructs tie up with Garrison’s model that the levels of motivation and SDL properly prepare the student’s frame of mind when entering a task for SDL. The difference in the pre and post test scores was significant - implying that their SDL of the OBSSM improved their understanding of the subject. There was also moderate correlation between the participants’ score and their level of motivation based on the ALPDEQ.

Conclusion: Remote teaching of BSS can be done and appreciated by learners if they have a reasonably high level of SDL.
Thesis
Keywords: Self-directed learning; Online teaching; Basic surgical skills